Multielemental Chemical Analysis of Elements in Mandibular Bone and Teeth in the Rat - Němec, I; Smrčka, V; Mihaljevic, M; Mazánek, J; Pokorný, J (Folia biologica, 2018)
The purpose of the study was to test the hypothesis of different distribution spaces of elements in the rat mandibular bone and teeth. We used six adult males of Wistar laboratory rats for the study. After killing the animals, we extracted the molars and removed incisor crowns. The mandibular bone was divided into four parts (mesial-central-distal-ridge). Inductively coupled plasma mass spectrometry was used to determine the presence of 41 elements in the bone and tooth. Evidence of 14 elements was found in all samples (incisors-molarsbone). Generally, significant differences between the left and right side were found for K and Rb in the bone locations. As regards statistically significant differences in incisors-molars-bone locations, the elements for which these differences were found for all comparisons are listed as incisors versus individual molars, incisors versus bone locations, and individual molars versus bone locations: a) incisors-molars: Ba, Mn, Mo, Sr, Zn, K, Mg and Rb; b) incisors-bone: Fe, K, Mg, Mn, Na, Zn and Ba; c) molars-bone: Mn, Mo, Na and Mg. Statistically significant differences were also found between molars for Fe, Mg, Mn, and Sr and between bone locations for Ba, Ca, Mn, Sr, K, Rb, Zn, Mo, Mg, and Na. The elements Cu, Ni and Co were without pronounced differences. Twenty-seven elements were below the detection limit. Our results indicate different distributions of some elements in the rat mandibular incisors-molars-bone. We assume that the knowledge of chemical element contents in the laboratory rat bone and teeth will prove useful in experimental research of both these hard tissues.
Keywords: mandibula; Animals; mužské pohlaví; Mandible; Rats, Wistar; potkani Wistar; zuby; zvířata; Tooth; Elements; analýza rozptylu; Analysis of Variance; Male; prvky